(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
Croatia has been seeking to achive pre-war results in tourism since its independence. Rural tourism in Croatia based on family farma faces a number of problems legal foundations, the involement of local communities, inadequate entepreneur support etc. The political will for development exists, but there is lack of willingness and the ability to get things started, which results in the closure of family farma who cannot cope with the parallel job of agriculture and tourism. Arriving guests certainly want a new type of tourism: peace, clean environment, cultural intangible and tangible treasures, all without the noise and stress; and Croatia can definitely offer it, either in coastal or inland areas with traditional food and drinks. The destinations connection is not satisfactora. there is also an evident lack of legislation and regional spatial development plans for sustainable tourism which is a prerequisite for successful tourism. With these plans presumptins accepted, Croatian tourism would become distinctive and inland and coastal branches of tourism could complement each other so that the customer can spend his vacation both in the continental ant the maritime part of the country, getting to know our culture and enjoy the traditional cousine.